Noninvasive Assessment of Liver Fibrosis in Patients with Chronic Hepatitis C (and Congenital Bleeding Disorders): Where Do We Stand? - Coppola, Antonio; Di Capua, Mirko; Conca, Paolo; Cimino, Ernesto; Tufano, Antonella; Cerbone, Anna Maria; Di Minno, Giovanni; Tarantino, Giovanni (Seminars in Thrombosis and Hemostasis, 2013)
The assessment and monitoring of liver fibrosis (LF) is a key issue in the management and definition of prognosis of patients with chronic hepatitis C (CHC). In this respect, despite recognized limitations (invasive nature, sampling errors, interobserver variability, nondynamic evaluation of LF), liver biopsy is traditionally considered the reference standard. These limitations stimulated the search for noninvasive approaches for the assessment of LF, particularly attractive in patients with hemophilia and other congenital bleeding disorders (CBD). In patients with congenital bleeding disorders (CBD), who often suffer from CHC because of the past use of nonvirally inactivated plasma-derived products, the risk of bleeding hamper to routinely obtain histological data for LF staging. A variety of methods have been proposed and, in some cases, validated in patients with CHC and other liver diseases, including biomarkers directly or indirectly associated with LF, often combined in scores or algorithms, and the more recently developed physical approaches, evaluating the properties of the liver parenchyma with instrumental techniques studying the propagation of specific signals, that is, transient elastography (TE), acoustic radiation force impulse imaging elastography, and magnetic resonance elastography. This review will describe the available strategies for noninvasive assessment of LF, with more details on the latter promising instrumental approaches. Moreover, although lacking of validation against liver biopsy, recent studies extending the use of noninvasive methods (particularly TE) in the setting of patients with CBD will be discussed.
Keywords: chronic hepatitis C; congenital bleeding disorders; hemophilia; liver biopsy; liver fibrosis; noninvasive tests; transient elastography